Efficiency of Insurance Companies in Cameroon: Does Corporate Governance Matter? - Mbanya, Tita Shipuh Victor; Elearzar, Jumbo Urie; Mimba, Tayong Desmond (Finance & Economics Review, 2024)
Purpose: The main objective of this study is to assess the level of efficiency of insurance companies in Cameroon and to examine the role of corporate governance in explaining this level of efficiency. Method: Using data extracted from the audited financial statements and reports of 15 insurance companies from 2010 to 2020, the study employs the output-oriented Malmquist index to measure the efficiency scores of non-life insurance companies in Cameroon. To examine the effect of corporate governance on the firms’ efficiency levels, we used the panel Tobit model. Result: Since insurance companies’ main mission is to protect against future risk occurrence while remaining financially viable, findings from data analysis revealed that the average efficiency level of sampled firms over the period of the study stands at 76.8%. Furthermore, results from the panel tobit analysis indicate that board gender diversity significantly enhances efficiency as well as board composition in terms of the number of foreigners on the board and ownership concentration measured by the number of shareholders compromise it. However, board size, presence of foreign executives, and foreign ownership were found to exert no significant effect on insurance companies in Cameroon. Implications: The study therefore recommends that corporate governance and regulatory oversight be strengthened by implementing measures that will go a long way to enhance corporate governance practices and ensure compliance with best practices and standards within insurance companies in Cameroon. A performance analysis commission should be created within the regulatory organ to assess, rank, and recommend best practices to the insurance firms.